DIGITAL INFORMATIONAL AND EDUCATIONAL ENVIRONMENT AS A MEANS OF EDUCATING A COMPETITIVE GRADUATE OF A TECHNICAL UNIVERSITY (ON THE EXAMPLE OF PENZA STATE TECHNOLOGICAL UNIVERSITY) - Kozlova, Natalia (Revista Inclusiones, 2020)
The problem of this study is the implementation of a competence-based approach to the information support of the educational work of a technical university, by introducing into practice a complex of elements of the digital informational and educational environment (DIEE), which serve as a systematic methodological support of the educational process, which is a single information professional field for teachers, an individual educational space for students, and a means of assessing the educational level of graduates by future employers. The purpose of this study is to improve the complex of methods, forms, and means of education, which allow to compare the results of the development of the personality of students (personal growth) with their achievements in educational and practical activities with the level of competence formation. From the point of view of a scientific approach, the research is aimed at identifying and disclosing contradictions between: the high demands of employers to the quality of competitive graduates of technical universities, who possess not only professional, but also general cultural competencies that ensure successful social activity in society, on the one hand, and the imperfection of information technology applied in education, on the other. To assess the results of the study, the following methods were used: diagnostics, comparison of standard and current indicators, analysis of the relationship of quantitative and qualitative indicators. The study involved 3,500 students annually. The practical significance of the study lies in the developed set of DIEE elements, which are a set of information, educational, telecommunication resources and technologies that form a single educational system of the university.